2021
DOI: 10.1002/jclp.23103
|View full text |Cite
|
Sign up to set email alerts
|

Negative mood regulation expectancies moderate the effect of childhood maltreatment on compulsive buying

Abstract: Objective Two studies investigated childhood maltreatment, alexithymia—the inability to identify one's mood—and negative mood regulation expectancies (NMRE)—confidence that one can alleviate one's negative moods—as predictors of compulsive buying (CB). Method Participants were recruited from internet CB forums and undergraduate psychology classes. Online, they completed questionnaires and a behavioral task that assessed impulsive spending. Results In Study 1 (N = 646), analyses indicated that NMRE, alexithymia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
2
2
0
1
Order By: Relevance
“…While their findings are not specific to impulse spending specifically, they showed that ACEs are linked to emotion dysregulation which may lead to difficulties in later life across a range of domains. The current findings also align with Shin et al ( 2018 ) who showed that ACEs are related to impulsivity in later life, as well as Kaur and Mearns ( 2021 ) who found that negative mood regulation expectancy moderated the link between childhood adversity and impulsive spending. These findings are also consistent with research showing that mood prior to spending increases the likelihood of impulsive spending (Ozer & Gultekin, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…While their findings are not specific to impulse spending specifically, they showed that ACEs are linked to emotion dysregulation which may lead to difficulties in later life across a range of domains. The current findings also align with Shin et al ( 2018 ) who showed that ACEs are related to impulsivity in later life, as well as Kaur and Mearns ( 2021 ) who found that negative mood regulation expectancy moderated the link between childhood adversity and impulsive spending. These findings are also consistent with research showing that mood prior to spending increases the likelihood of impulsive spending (Ozer & Gultekin, 2015 ).…”
Section: Discussionsupporting
confidence: 91%
“…Childhood trauma showed a weak but significant positive correlation with impulsive spending, indicating that greater exposure to childhood trauma increases the likelihood that an individual will impulsively spend in later life, supporting Hypothesis A. This aligns with previous findings showing that childhood maltreatment is linked to greater compulsive spending (Kaur & Means, 2021 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Studies have supported the hypothesis that alexithymia may constitute a stable personality trait, strongly influenced and caused by many factors, including stressful life and early traumatic experiences, which may, in turn, lead to increased vulnerability both to EDs and addictive disorders (Lane et al, 2000;Lyvers et al, 2019;Shank et al, 2019;Lenzo et al, 2020). According to Kaur (2019), individuals who experienced more stressful childhood experiences and reported less ability to identify their moods (i.e., alexithymia) were more likely to use an addictive behaviour as a maladaptive coping mechanism. In addition, posttraumatic disorders are significantly more recurrent in young people in treatment for addiction and EDs than those without them, and are associated with a costlier treatment and worse prognosis (Wang et al, 2020;Momeñe et al, 2022a).…”
Section: Discussionmentioning
confidence: 99%
“…Dissosiyasyonun ve aleksitimi belirtilerinin çevrimiçi kompulsif satın alma bir risk faktörü olduğu önceki çalışmalarda da gösterilmiştir (35,50,51). Bulguların birbiriyle paralelliği çevrimiçi kompulsif satın almanın, sıkıntı ve diğer olumsuz duygudurumlardan geçici olarak uzaklaşmak için bir araç olarak kavramsallaştırılmasını destekler niteliktedir (52).…”
Section: çEvrimiçi Kompulsif Satın Almaunclassified